Civic death as a mechanism of retributive punishment: Academic purges in Turkey - Özdemir, Seçkin Sertdemir (Punishment & society, 2021)
In an era when authoritarian governments increasingly target academics, Turkey’s 2016 purge of more than 6,000 academics and their diminution to civic death is conspicuous in its cruelty. Although unprecedented, this is not the first time that Turkish academics have been punished en masse. By looking at the tools with which academics have been expelled from educational institutions, the public sphere, and the political body, I attempt to develop a nuanced understanding of the interconnected forms of punishment directed towards academic citizens as knowledge producers. I suggest that the 1980 coup accomplished three things: it introduced new mechanisms of punishment based on a logic of retribution instead of compensation; it changed the legal system into a regime of exception; it transformed academics into patriotic worker-citizens. The latest purges have brought an additional change in the status of academics’ citizenship, rendering them as disposable citizens forever at risk of being targeted as the ‘civic dead’.